2017
DOI: 10.1093/cid/cix777
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Venous Thromboembolism Following Hemorrhagic Fever With Renal Syndrome: A Self-controlled Case Series Study

Abstract: A significantly increased risk for VTE was found in the time period following HFRS onset. It is important to keep this in mind and monitor HFRS patients, and possibly other viral hemorrhagic fever patients, for early symptoms of VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…Corroborating this study, a related report demonstrated a significantly increased risk of acute myocardial infarction and stroke during HFRS . More recently, risk of thromboembolism following HFRS has also been addressed where a significantly increased risk of venous thromboembolism was observed early after on onset of HFRS .…”
Section: Acute and Possible Long‐term Effects Of Clinical Puuv And Otsupporting
confidence: 63%
“…Corroborating this study, a related report demonstrated a significantly increased risk of acute myocardial infarction and stroke during HFRS . More recently, risk of thromboembolism following HFRS has also been addressed where a significantly increased risk of venous thromboembolism was observed early after on onset of HFRS .…”
Section: Acute and Possible Long‐term Effects Of Clinical Puuv And Otsupporting
confidence: 63%
“…Three-dimensional printing is embraced by students and shows the innovation of new, exciting technology. Two studies have investigated the accuracy in answering questions among students in 3D printing groups and conventional groups [39,40]. Students in the 3D printing groups showed more accuracy in answering questions compared with students in the conventional groups ( Supplementary Table).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies investigated the answering accuracy in the 3D printing and conventional groups [39,40]. The two studies are descriptive and do not incorporate data.…”
Section: Accuracymentioning
confidence: 99%
“…We have shown that HFRS is a risk factor for both arterial and venous thrombosis. 5 6 We here report a case of a patient with HFRS with prolonged thrombocytopenia who developed thrombosis shortly after receiving platelet transfusion.…”
Section: Introductionmentioning
confidence: 96%